2021
DOI: 10.52728/ijjm.v2i3.279
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Business Environment in Construction Service Industry in DKI Jakarta Indonesia

Abstract: This study aims to specifically analyze the business environment in the construction service industry in DKI Jakarta, by using an external and internal dimension factor approach. The dimensions of external factors include several indicators such as political, economic, social, and technological indicators. While the internal factor dimensions consist of indicators of corporate culture, corporate structure, and corporate resources. The analysis technique uses Structural Equation Model (SEM) with SmartPLS. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Later during pandemic period, some authors also discussed about financing issue in a state Triyawan & Fendayanti, 2021). Contractor issue was also discussed with particular about their human resource efficiency in a capital city (R. Santoso & Permana, 2021). (Figure 1)…”
Section: Resultsmentioning
confidence: 99%
“…Later during pandemic period, some authors also discussed about financing issue in a state Triyawan & Fendayanti, 2021). Contractor issue was also discussed with particular about their human resource efficiency in a capital city (R. Santoso & Permana, 2021). (Figure 1)…”
Section: Resultsmentioning
confidence: 99%
“…This is because the business environment can influence important variables. The business influences the environment in business strategy planning (Santoso et al, 2021).…”
Section: G Environmental Aspectsmentioning
confidence: 99%
“…This study will refer to several research results that are relevant to the research topic, provide inspiration to raise the topic of research in the MSME sector: (1) Research related to Aren Sugar by Fikry, Muis & Tangkesalu (2019) that analyzing the income and feasibility of Aren Sugar business in one of the villages in Central Sulawesi; (2) Research by Manyati and Mutsau's (2021) indicated the need to expand skills in managing small and medium-sized enterprises in a sustainable manner to overcome the crisis; (3) Research by Ningsih (2020) to determine the feasibility and to determine the development strategy of the small industry sector; (4) Research by Ramadhanty, Suryana and Aryani (2020) regarding the feasibility analysis of the laundry business in terms of various aspects; (5) Research by Santoso, Permana & Abdullah (2021) about Business Environment in Construction Service Industry in DKI Jakarta.…”
Section: Introduction Background Statementmentioning
confidence: 99%